Aplikasi Layanan Bebas Pustaka Berbasis Web terhadap Kepuasan Pemustaka di Perpustakaan Universitas Hasanuddin Makassar - Andi Nur Fadilah; Iskandar Iskandar; Umar Sulaiman (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to analyze the level of user satisfaction and the impact of a web-based library clearance service application on user satisfaction at the Library of Hasanuddin University, Makassar. A descriptive quantitative method was used with 99 respondents, all of whom were students who had used the application. Data were collected through an online questionnaire and analyzed using SPSS and Microsoft Excel. The results show that user satisfaction with the application is categorized as